Structural identification of concrete arch dams by ambient vibration tests - Sevim, Baris; Altunisik, Ahmet Can; Bayraktar, Alemdar (TECHNO-PRESS, 2013)
Modal testing, widely accepted and applied method for determining the dynamic characteristics of structures for operational conditions, uses known or unknown vibrations in structures. The method's common applications includes estimation of dynamic characteristics and also damage detection and monitoring of structural performance. In this study, the structural identification of concrete arch dams is determined using ambient vibration tests which is one of the modal testing methods. For the purpose, several ambient vibration tests are conducted to an arch dam. Sensitive accelerometers were placed on the different points of the crest and a gallery of the dam, and signals are collected for the process. Enhanced Frequency Domain Decomposition technique is used for the extraction of natural frequencies, mode shapes and damping ratios. A total of eight natural frequencies are attained by experimentally for each test setup, which ranges between 0-12 Hz. The results obtained from each ambient vibration tests are presented and compared with each other in detail. There is a good agreement between the results for all measurements. However, the theoretical fundamental frequency of Berke Arch Dam is a little different from the experimental.
Keywords: arch dams; ambient vibration test; dynamic characteristics; signal processing; Construction & Building Technology; Engineering; Materials Science